REDESIGN ERGONOMIC RUBBISH BIN EFFICIENT BASED ON ANTHROPOMETRY DATA - Resy Kumala Sari; Raka Tabagus (Jurnal Teknik Industri Terintegrasi, 2021)
The rubbish bin is needed globally because of the place to collect the rest of the rubbish. The rubbish bin is available in the public area, home, and office. This study redesigned the Rubissh bin to make it more ergonomic and efficient when used and recruited 100 students of Universitas Pahlawan Tuanku Tambusai (45 female participants and 55 male participants) by measuring their anthropometry of the human body. Anthropometric data measured in the form of Lebar Bahu (LB), Tinggi Kepalan Tangan (TKT), Tinggi Pinggang Berdiri (TPB), Lebar Telapak Tangan (LTT), Lebar Telapak Kaki (LTK), and Jangkauan Tangan Kedepan (JTD). After that, the data in the normality test can be seen that the chi-square <chi square table, that mean is normally distributed. The uniformity test states that the 6 anthropometric data were uninformed, and the data sufficiency test shows that the results of data processing were sufficient to represent all samples (N '<N). The results of testing and calculation of percentiles can be measured in redesign ergonomic efficient rubbish bin based on anthropometric data in the form of LB (P5: 34.61 cm), TKT (P95: 81.75 cm), TPB, (P95: 106.67 cm), LTT (P95: 10.28 cm), LTK (P95: 11.95 cm), JTD (P95: 83.27 cm). Therefore, the redesign of the rubbish bin has been determined in an ergonomic size so that it can be used practically, safely, and comfortably. Keywords: Antropometric Data, Ergonomic, Redesign, Rubbish Bin.